Analysis Of The Influence Of Inflation, Exchange Rate And Current Transaction Deficit On Government’s Foreign Debt - Rina Apriliani; Merissa Fermica Iskandar; Teguh Prakoso; Susanto; Musran Munizu (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The goal of the study is to evaluate the impact of Indonesia’s government foreign debt on the country’s current account deficit, exchange rate, and inflation before and after the world financial crisis. Ordinary Least Squares (OLS) is the analytical technique used. According to regression analysis, the current account deficit, currency rate, inflation, and the global financial crisis account for 90% of the official foreign debt. The analysis’ findings indicate that the exchange rate and the current account deficit have a negative and considerable impact on the government’s foreign debt. The Indonesian government debt is strongly and favorably influenced by the inflation rate.